Compactness Property of Fuzzy Soft Metric Space and Fuzzy Soft Continuous Function - Sabri, Raghad I. (Iraqi Journal of Science, 2021)
The theories of metric spaces and fuzzy metric spaces are crucial topics in mathematics. Compactness is one of the most important and fundamental properties that have been widely used in Functional Analysis. In this paper, the definition of compact fuzzy soft metric space is introduced and some of its important theorems are investigated. Also, sequentially compact fuzzy soft metric space and locally compact fuzzy soft metric space are defined and the relationships between them are studied. Moreover, the relationships between each of the previous two concepts and several other known concepts are investigated separately. Besides, the compact fuzzy soft continuous functions are studied and some essential theorems are proved.